ANALISIS MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS DALAM MENCEGAH PERILAKU KONTRAPRODUKTIF SISWA SD - Yulina Ismiyanti; Citra Setya Hadining Y, Jupriyanto (CV. Adiba Aisha Amira, 2025)
The research focuses on analyzing the Student Team Achievement Division (STAD) learning model in preventing counterproductive behavior of class IV students at SD Negeri Sembungharjo 02 Semarang City. The approach used in this research is a qualitative descriptive approach. This type of research is analysis. The instruments used were interviews, observations and questionnaires. Data analysis techniques use data collection, data reduction, data presentation, and data verification or conclusion. Testing the validity of the data uses triangulation techniques. Based on the data analysis of the results of this research, it can be concluded that the application of the Student Team Achievement Division (STAD) learning model is effective in preventing counterproductive behavior, through peer tutoring it increases positive student behavior such as respecting friends' opinions, establishing closeness between friends because basically group learning will generate student activity, both cognitive, affective and psychomotor, which will encourage collaboration, mutual give and take, both in words and actions, so that students avoid counterproductive behavior during the learning process.